Use of a dietary manipulation to deplete plasma tyrosine and phenylalanine in healthy subjects. - Sheehan, B; Tharyan, P; McTavish, S; Campling, G; Cowen, P (1996)
The aim of the present study was to lower plasma concentrations of tyrosine, the amino acid precursor of noradrenaline and to determine whether this manipulation impaired noradrenergic function as measured by the evening rise in concentrations of plasma melatonin. Eight healthy volunteers received three drinks: (i) an essential amino acid load with tyrosine, (ii) the same load without tyrosine and its precursor, phenylalanine and (iii) tap water. The tyrosine- and phenylalanine-deficient drink lowered plasma tyrosine by approximately 50% over 5 h. However, this did not alter the evening plasma melatonin levels compared to the other two drinks. The results suggest that amino acid loading produces a modest decline in plasma tyrosine levels but this does not lower noradrenergic neurotransmission in the pineal gland.